2016
DOI: 10.1002/poc.3665
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of allenes bearing 1,8‐diphenoxy or diaryloxyacridene moieties

Abstract: New allene compounds bearing 1,8‐diphenoxy or bis(3,5‐di‐tert‐butylphenyl) oxyacridene (diaryloxyacridene) moieties were synthesized. These compounds were more easily oxidized than Cl‐substituted compounds. The allene compounds were oxidized to generate thermally stable triplet carbenes. Electron spin resonance and electron spin transient nutation spectra of the oxidation reaction products suggested the generation of triplet species; however, the main isolated product from the 1,8‐diphenoxy allene was a cycliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Oxidations of allenes bearing 1,8‐diphenoxy or diaryloxyacridene moieties are performed by the research group of Professor Yohsuke Yamamoto to generate persistent triplet carbenes. They isolate a cyclized compound that is characterized by X‐ray analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidations of allenes bearing 1,8‐diphenoxy or diaryloxyacridene moieties are performed by the research group of Professor Yohsuke Yamamoto to generate persistent triplet carbenes. They isolate a cyclized compound that is characterized by X‐ray analysis.…”
mentioning
confidence: 99%
“…They isolate a cyclized compound that is characterized by X-ray analysis. [2] The research group of Professor Wolfram Sander reports the generation of a new sextet ground-state molecule, the 2,4,6trichloro-1,3-dinitrenophenoxyl radical, in the UV photolysis of the corresponding diazido precursor in argon at 5 K. [3] They found that the sextet molecule is formed in a stepwise fashion, with the triplet nitrene, the quartet nitreno radical, and the quintet dinitrene as intermediates that are detected by electron paramagnetic resonance spectroscopy.…”
mentioning
confidence: 99%